Aristotle on Theater and Dance: Connections to Present Time - Dermati, Aliki (Conatus - Journal of Philosophy, 2018)
Aristotle dealt with many facets of human creation and originality, and he could not, of course, miss the field of art. singing and acting. The philosopher himself dealt extensively with the subject of theater and dance in his work on Poetry. She placed great emphasis on the tragedy, for which she gave definition and preconditions, while dividing her building blocks into parts and quantities. Aristotle was mainly involved with dance (<orchisis) in the context of the tragedy, and in particular spoke about Parodos, the dance song of the dance, and about Stasis, the choral pieces that distinguished the episodes between them.